Implementation of Special Remission Policy for Prisoners in Penitentiary Class IIB Tasikmalaya, West Java, Indonesia - Kurniadi, Budi; Rena Dewi Munggaran, Nantia; Wandi , Yusef (International Journal of Psychosocial Rehabilitation, 2020)
Remission is a reduction in sentences for prisoners so that they behave well in serving their sentences in accordance with the objectives of the penal system in Indonesia. In reality, the implementation of the policy with the reality of granting remission collided with a political administrative mechanism, so that the amount was limited and not well realized. This study aims to describe and analyse in depth regarding the implementation of policies, uncovering inhibiting factors and judicial efforts, using the content of the policy and context of the implementation approach. The research method used is qualitative to uncover empirical reality by observing and exploring the behaviour of the object under study. The results of this study found that the factors that caused policy implementation were not optimal: (1) lack of understanding of the objectives of the policy content; (2) lack of competence and attitudes of policy implementers; (3) overlapping policy implementation; and (4) weak enforcement of regulations and implementation characteristics. It was also found that the development of Grindle theory in the dimensions of policy content was attitude, ethical behavior, and policymaker acceptability. Whereas in the context of the implementation dimension is holistic policy evaluation, interagency coordination, and law enforcement.